Effects of regular, glulisine, and aspart insulin on vascular endothelial growth factor and angiotensinogen expression in hyperglycemic retinal pigment epithelial (RPE) and human retinal endothelial cells (HRECs) - Sanie-Jahromi, Fatemeh; Khosravi, Abtin; Hadianfard, Hooman; Nowroozzadeh, M. Hossein (Frontiers in Ophthalmology, 2025)
IntroductionDiabetic retinopathy (DR) is a leading cause of vision loss and is primarily driven by chronic hyperglycemia, which induces retinal vascular damage through mechanisms involving vascular endothelial growth factor (VEGF) and the renin-angiotensin system (RAS). This study investigated the effects of hyperglycemia and different insulin formulations—regular, glulisine, and aspart—on VEGF-A and angiotensinogen (AGT) gene expression in two human retinal cell types: retinal pigment epithelial (RPE) cells and human retinal microvascular endothelial cells (HRECs).MethodsCells were cultured from donor tissue and exposed to physiologic and hyperglycemic glucose concentrations, with or without insulin treatment. Gene expression levels were quantified using real-time PCR.ResultsHyperglycemia significantly upregulated VEGF-A and AGT in both RPE and HREC cells (e.g., VEGF-A in RPE: 2.62-fold, P = 0.001; AGT in RPE: 3.32-fold, P = 0.093), supporting a role for both osmotic and glucose-specific pathways. Among insulin treatments, regular insulin significantly reduced VEGF-A expression in both RPE (0.72-fold, P = 0.033) and HRECs (0.57-fold, P = 0.009). In contrast, aspart and glulisine had modest effects on VEGF-A in HRECs (0.82-fold each; P = 0.035 and P = 0.060, respectively) and no significant impact in RPE cells. Regarding AGT, aspart insulin showed the most consistent suppressive effect, reducing expression in both RPE (0.15-fold, P < 0.001) and HRECs (0.22-fold, P = 0.004). Glulisine significantly increased AGT in RPE (1.56-fold, P = 0.009) but reduced it in HRECs (0.58-fold, P = 0.074). Regular insulin showed no effect on AGT in RPE (P = 0.680) and a non-significant increase in HRECs (1.36-fold, P = 0.097).DiscussionThese findings highlight the differential biological effects of insulin analogues and suggest that aspart insulin, in particular, may offer therapeutic benefits beyond glycemic control by modulating both VEGF-A and RAS-related pathways. Tailored insulin therapies could represent innovative strategies for managing or slowing the progression of diabetic retinopathy.